Response of Bread Wheat Crop to the Spray of Alcoholic Sugars and A balanced Mineral Fertilizer in the Central Region of Iraq - Ati, Alaa Salih; Abd-Aljabar, Sana; Abed, Hasan Flayyih (Journal of Kerbala for Agricultural Sciences, 2022)
Two field experiments were conducted during the season 2021-2022 in central Iraq represented by the Al-Muthanna governorate - Al-Majd District and Al-Qadisiyah governorate / Al-Nouriah Research Station to determine the productivity of the Baghdad 3 cultivar from spray foliar fertilization of Macro and Micro elements with alcoholic sugars and half the fertilizer recommendation for addition floor, three treatments were used for fertilization: T1 as the control treatment and T2 with alcoholic sugar fertilization at a concentration of 20 g.L-1 + the fertilizer combination of Macro and Micro elements, and T3 with alcoholic sugar fertilization at a concentration of 40 g.L-1 + the fertilizer combination of Macro and Microelements, at irrigation 55% of the water is depleted available water. The results showed that the seasonal water consumption was 437.5 and 425 mm in Al-Muthanna and AL-Qadisiyah locations, respectively and spraying with alcoholic sugars and fertilizer combination (balanced mineral fertilizer and micro-elements) during the different growth stages achieved significant differences in plant height, leaf area, number of branches plant-1 and chlorophyll content and it showed the success of the integrated fertilizer combination to spray nitrogen, potassium and microelements in the presence of alcoholic sugars with sorbitol with fertilization with triple superphosphate before planting 20 kg ha-1, and urea fertilizer 156 kg ha-1 under the conditions of the current experiment. The total yield of wheat was (4000 kg ha-1) and (5300 kg ha-1) at T2 and T3 fertilization treatment, respectively, compared to T1 treatment (5780 kg ha-1) in Al-Muthanna province. In Al-Qadisiyah Governorate location, the weight of the total yield increased with the fertilization treatments T2 (3768 kg ha-1) and T3 (4332 kg ha-1) compared to the treatment of T1 fertilization (3264 kg ha-1).